2015
DOI: 10.1149/2.0211510jes
|View full text |Cite
|
Sign up to set email alerts
|

3-(1,1,2,2-Tetrafluoroethoxy)-1,1,2,2-tetrafluoropropane as a High Voltage Solvent for LiNi1/3Co1/3Mn1/3O2/Graphite Cells

Abstract: A new electrolyte based on fluorinated 3-(1,1,2,2-tetrafluoroethoxy)-1,1,2,2-tetrafluoropropane (F-EPE) solvent is developed to decrease the capacity fading of LiNi 1/3 Co 1/3 Mn 1/3 O 2 /graphite lithium-ion batteries (LIBs) cycled in the voltage range of 3.0-4.5 V (vs. Li/Li + ). The linear sweep voltammetry (LSV) and cyclic voltammetry (CV) indicate that F-EPE has an oxidation potential of more than 5.4 V vs. Li/Li + , which is higher than traditional solvents and enlarges the oxidative window of electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…38 Zhang et al 3 LiNi 1/3 Co 1/3 Mn 1/3 O 2 /graphite electrodes cycled in a voltage range of 3.0−4.5 V (vs. Li/Li + ). 39 Luo et al applied F-EPE for improved cycling of cells containing high-voltage cathodes LiNi 0.5 Mn 1.5 O 4 . 40 The stability and performance of these electrolyte solutions may also depend on the presence of various impurities.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Zhang et al 3 LiNi 1/3 Co 1/3 Mn 1/3 O 2 /graphite electrodes cycled in a voltage range of 3.0−4.5 V (vs. Li/Li + ). 39 Luo et al applied F-EPE for improved cycling of cells containing high-voltage cathodes LiNi 0.5 Mn 1.5 O 4 . 40 The stability and performance of these electrolyte solutions may also depend on the presence of various impurities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that the electrolyte solutions containing fluorinated carbonates and F-EPE ether have superior electrochemical stability compared with the EC/EMC-based electrolyte solutions. Wang et al utilized F-EPE to improve the cycling stability of full cells based on LiNi 1/3 Co 1/3 Mn 1/3 O 2 /graphite electrodes cycled in a voltage range of 3.0–4.5 V (vs. Li/Li + ) . Luo et al applied F-EPE for improved cycling of cells containing high-voltage cathodes LiNi 0.5 Mn 1.5 O 4 …”
Section: Introductionmentioning
confidence: 99%
“…Even at higher C-rates, the cell still achieved a capacity of 142.0, 132.0, 114.4 mAh g -1 at 1 C, 2 C and 5 C (Figure 6.4d), respectively. These values compete well with those already reported in literature for lithium-ion batteries with advanced configuration[262,263], due to the high C-rate performance of MP-NCM.Figure 6.4e reveals the cycling performance of the full cell. After initial few cycles at 0.1 C for activation, the cell was cycled at 1 C with 147.5 mAh g -1 of capacity delivered.…”
supporting
confidence: 88%
“…4a–d ), a pair of clear redox peak stands for Li + extraction/insertion in the MCMB. 29 A weak reduction peak located at 1.1–1.2 V ( Fig. 4b and d ) should be attributed to participation of SEI construction by fluorinated ether TFEE.…”
Section: Resultsmentioning
confidence: 88%